Pontine and Cerebellar Development in Low-Birthweight Infants at Term-Equivalent Age. Issue 2 (June 2022) - Hayakawa, Katsumi; Tanda, Koichi; Nishimura, Akira; Kinoshita, Daisuke; Nishimoto, Masakazu; Yoshida, Mariko; Kizaki, Zenro; Ohno, Koji
Purpose: Pontine and cerebellar developments were investigated in low-birthweight (LBW) infants at term-equivalent age (TEA) using magnetic resonance imaging (MRI). Methods and Materials: The study subjects were a consecutive series of LBW infants born with a birthweight of <1, 500 g. Among them, 51 neonates with an extremely low birthweight (ELBW) and 65 neonates with a very low birthweight (VLBW) infants underwent MRI exam at TEA. We measured the pontine anteroposterior diameter (APD), cerebellar vermian APD and height, and cerebellar transverse width using midline sagittal and axial T1 weighted images. Twenty term neonates with neonatal asphyxia showing a normal pattern and white matter injury on MRI exam served as a control group. Gender differences in these parameters were compared among the LBW groups. Result: Pontine APD in the ELBW group was significantly less than that in the control group. Cerebellar vermian APD and height were similar among the 3 groups. However, cerebellar transverse width was significantly less in the LBW groups than in the control group. A significant gender-related difference in pontine APD was evident, but cerebellar measurements showed no significant gender difference. Conclusion: LBW infants showed significantly developmental delay in terms of pontine APD and cerebellar width. A sex difference in pontine growth was evident among LBW infants.